KETERKAITAN MIGRASI PENDUDUK DAN PEREKONOMIAN DI JAWA TENGAH - Reny Yesiana; Wiwandari Handayani; Renni Nur Hayati (JURNAL LITBANG PROVINSI JAWA TENGAH, 2015)
Population dynamics is one of the aspects be considered in regional planning. Population important to be noticed and taken into consideration because the population is subject and object of development in order to achieve prosperity. Migration is one of the three basic factors that influence the growth of the population, in addition to births (fertility) and death (mortality). Migration can increase the number of population if the number of people who go into an area more than the number of people who leave the region. This study examines the deeper dynamics of migration that occurred in Central Java. This study used a qualitative descriptive statistical analysis and map overlay analysis. Based on the results of studies that have been done that most region/ cities in Central Java included in quadrant III as many as 21 region/ cities (60%) and in quadrant I, as many as 11 region/ cities (31%). While the category quadrant II is only one region(3%) and quadrant IV only 2 region (6%).